2016
DOI: 10.5430/jnep.v7n1p66
|View full text |Cite
|
Sign up to set email alerts
|

A theory guided nursing intervention for management of hypertension among adults at rural area

Abstract: Background and objective: Hypertension is one of the most important preventable causes of premature morbidity and mortality in the world. Many people with hypertension both in developing and developed countries have no adequate control of their blood pressure. Lifestyle modification and adherence to antihypertensive drugs play an important role in controlling hypertension and in preventing its long-term complications. Aim: This study was conducted to assess the effect of application of Pender's Health Promotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A different study aimed to assess the effect of application of HPM on management of hypertension among 150 adults in Egypt, showed that there was statistical significant improvement among the study group than the control group at the posttest of health-promoting behavior, and the highest mean score was in the posttest of nutrition dimension followed by medication adherence, stress management and physical activity, but smoking had no statistical significant improvement [18]. Moreover, a significant difference among 80 health volunteers in Iran found between the mean scores of physical activity and other structures of HPM in the experimental group after the intervention and its score before intervention [19].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A different study aimed to assess the effect of application of HPM on management of hypertension among 150 adults in Egypt, showed that there was statistical significant improvement among the study group than the control group at the posttest of health-promoting behavior, and the highest mean score was in the posttest of nutrition dimension followed by medication adherence, stress management and physical activity, but smoking had no statistical significant improvement [18]. Moreover, a significant difference among 80 health volunteers in Iran found between the mean scores of physical activity and other structures of HPM in the experimental group after the intervention and its score before intervention [19].…”
Section: Resultsmentioning
confidence: 99%
“…The second category included eleven studies which evaluated the HPM as a mean to predict physical activity (PA) in a sample of Iranian adolescent boys [7], compared perceived self-efficacy, exercise benefits, exercise barriers, and commitment to exercise between patients diagnosed with osteoporosis and osteoarthritis, and assessing the influence of perceived exercise self-efficacy, exercise benefits, and barriers on commitment [8], explored perceived exercise self-efficacy, benefits and barriers, and commitment to exercise among Jordanians with chronic illnesses [14], explored perception of exercise benefits and barriers among Jordanian patients' with End Stage Renal Disease (ESRD) [11], used HPM to provide insight into the relationship between dietary and fluid non-adherence, depressive symptoms, quality of life, perceived barriers and benefits of exercise, and perceived social support among Jordanian patients with ESRD receiving hemodialysis [9], conducted an evaluation of an educational program based on the HPM and stages of change to improve physical activity (PA) behavior among Iranian adolescents [10], used Pender's HPM to describe and identify the predictors of health-promoting behaviors in Nepalese migrant workers in Korea [13], examined the psychometric properties of the Arabic version of Bandura's Exercise Self-Efficacy scale (ESE-A) among Jordanian patients with different chronic diseases [16], assessed the effect of application of Pender's HPM on management of hypertension among adults in rural area [18], examined the impact of performing a HPM intervention on physical activity of the health Volunteers [19], and investigated the effect of Pender's HPM to improve the nutritional behavior of overweight and obese women admitted to Fatemiyeh…”
Section: The Purposes Of the Reviewed Studiesmentioning
confidence: 99%
See 3 more Smart Citations